Removal of triazine-based pollutants from water by carbon nanotubes: Impact of dissolved organic matter (DOM) and solution chemistry. (1st December 2016) - Engel, Maya; Chefetz, Benny
Abstract: Adsorption of organic pollutants by carbon nanotubes (CNTs) in the environment or removal of pollutants during water purification require deep understanding of the impacts of the presence of dissolved organic matter (DOM). DOM is an integral part of environmental systems and plays a key role affecting the behavior of organic pollutants. In this study, the effects of solution chemistry (pH and ionic strength) and the presence of DOM on the removal of atrazine and lamotrigine by single-walled CNTs (SWCNTs) was investigated. The solubility of atrazine slightly decreased (∼5%) in the presence of DOM, whereas that of lamotrigine was significantly enhanced (by up to ∼70%). Simultaneous introduction of DOM and pollutant resulted in suppression of removal of both atrazine and lamotrigine, which was attributed to DOM-pollutant competition or blockage of adsorption sites by DOM. However the decrease in removal of lamotrigine was also a result of its complexation with DOM. Pre-introduction of DOM significantly reduced pollutant adsorption by the SWCNTs, whereas introduction of DOM after the pollutant resulted in the release of adsorbed atrazine and lamotrigine from the SWCNTs. These data imply that DOM exhibits higher affinity for the adsorption sites than the triazine-based pollutants. In the absence of DOM atrazine was a more effective competitor than lamotrigine for adsorption sites in SWCNTs. However, competition between pollutants in the presence of DOM revealed lamotrigine as the better competitor. Our findings help unravel the complex DOM–organic pollutant–CNT system and will aid in CNT-implementation in water-purification technologies. Graphical abstract: Highlights: Removal of triazine-based pollutants by CNTs was systematically studied. Atrazine, lamotrigine and DOM compete over the same adsorption sites within CNTs. DOM decreases the removal of triazine-based pollutants. Solubility of lamotrigine was greatly influenced by solution chemistry and DOM.